Evaluation of safety benefits of the road cross section upgrading on the Okahandja Karibib road in Namibia - Hepkema, Watze (Department of Civil Engineering, 2019)
Globally, road fatalities have reached pandemic proportions. The Decade of Action for Road Safety of the United Nations has the aim to reduce road fatalities (UN, 2017, page 23). This dissertation investigates the Global and Namibian road safety status. The global road fatality rate is 17.7 deaths per 100 000 population, and the Africa continent has 26.6 deaths per 100 000 population (WHO, 2015, page 6). Namibia, in 2016, had around 34 deaths per 100 000 population (MVA, 2016, page 5). Namibia, with a small population of 2,2 million people (Census, 2011), is part of the Decade of Action. The crashes in Namibia are reviewed to determine if there are any trends on where and when they occur. The three most frequent crashes in Namibia are roll-over crashes, at 29% of all crashes, collisions at 28% of all crashes, with head-on crashes the most fatal and pedestrian crashes, which account for 22% of all crashes (MVA, 2016, page 5) International reports on mitigation measures for these three types of crashes were reviewed. The trunk road network of Namibia forms the major transport corridor network that connects the major cities and neighbouring countries. Trunk roads are generally 7.0m wide bitumen surfaced roads with 2.0m gravel shoulders. The Okahandja to Karibib road was upgraded with wider lanes, surfaced shoulders and six passing lane sections. The upgrading was completed in 2012 and this dissertation evaluated the road safety improvements due to the geometrical upgrading of the road, by comparing the road with an adjacent section that has not been upgraded. The National Road Safety Council provided crash data of Namibia from 2007 to 2016. Before construction, roll-over crashes were the most frequent fatal crash type. In the post-construction period no fatal roll-over crashes occurred. The number of collisions has not substantially decreased, but there is a decline in the severity of the crashes. The study concluded that Namibia has a high road fatality rate in comparison with the global road fatalities. The road upgrading of the Karibib Okahandja road did improve the road safety of the road, but the road fatalities are still high compared with international fatality rates.